Oily Fish Consumption Modifies the Association between CD36 rs6969989 Polymorphism and Lipid Profiles in Korean Women - Shin, Yoonjin; Kim, Yangha (Preventive nutrition and food science, 2016)
The aim of this study was to investigate the association of CD36, a class B scavenger receptor, rs6969989 polymorphism with the serum lipid profiles in Korean women, together with their modulation by oily fish consumption. Subjects were participants from the Korean Genome Epidemiology Study (KoGES), which was initiated in 2001 as a large-scale. A total of 4,210 women aged 39 to 70 were included in this study. Data were collected using self-administered questionnaires, anthropometric measurements, and blood chemical analysis. Dietary intake was analyzed using a semi-quantitative food frequency questionnaire. The minor allele frequency for rs6969989 was found in 12% of this population. Homozygotes minor G allele at the rs6868989 exhibited significantly higher high density lipoprotein cholesterol (HDL-C) concentrations ( -trend=0.043) and lower fasting glucose ( -trend=0.013) than major allele A carriers. The risk of low HDL-C was significantly lower in homozygotes for the G allele than the A allele carriers ( -trend=0.032). Gene-diet interaction effects between rs6969989 and oily fish intake were significantly associated with the risk of dyslipidemia ( -interaction= 0.004). Subjects with homozygotes minor G allele and high oily fish intake generally had a lower risk of dyslipidemia than did those with major allele homozygotes and low oily fish intake. These findings supported that oily fish consumption may modulate the contributions of CD36 rs6969989 on genetic predisposition to the risk of dyslipidemia.